PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP KUALITAS LABA - Sri Ayem; Safrudin S Safrudin (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to examine the effect of capital structure, firm size and profitability on earnings quality. The sample used in this study is food and beverage companies listed on the IDX for the 2019-2020 period. The population of this study amounted to 26 food and beverage companies, using purporsive sampling technique and an observation period of 2 years so that 40 samples of observation data were obtained. The data needed in this study were obtained from the publication of financial statements in the Indonesia Stock Exchange. The data analysis method used to test the hypothesis is multiple linear regression analysis. The analysis was carried out using SPSS version 25. The results of this study indicate that capital structure has no effect on earnings quality. Firm size has a positive and significant effect on earnings quality. Profitability has no effect on earnings quality.